Two novel TSC2 mutations in pediatric patients with tuberous sclerosis complex: Case report. Issue 29 (July 2018) - Gao, Shan; Wang, Zhiling; Xie, Yongmei
Abstract: Rationale: Tuberous sclerosis complex (TSC) is a rare autosomal dominant disorder. The TSC1 and TSC2 genes have been identified as pathogenic genes. Patient concerns: In this report, we are discussing a novel frameshift mutation and a novel missense mutation in the TSC2 gene. Diagnoses: The two cases discussed in this study met the latest diagnostic criteria for TSC published by the International Tuberculosis Sclerosis Complex Consensus Conference in 2012. Interventions: High-throughput sequencing and multiplex ligation-dependent probe amplification (MLPA) were used to examine tuberous sclerosis complex (TSC)-related genes ( TSC1 and TSC2 ) and their splicing regions using peripheral blood DNA from two probands in two families with TSC and to identify the genetic mutation sites. Amplification primers were designed for the mutation sites, and polymerase chain reaction and Sanger sequencing were used to verify the peripheral blood DNA sequences from the probands and their parents. Outcome: Proband 1 had the c.1228 (exon 12)_c.1229 (exon 12) insG (p.L410RfsX11) heterozygous mutation in the TSC2 gene (chr16), which was a new frameshift mutation. Proband 2 had the c.4925G>A (exon 38) (p.G1642D) heterozygous mutation in the TSC2 gene (chr16), which was a new missense mutation. Lessons: These two novel mutations may be pathogenic mutations for TSC, and their association with the disease needs to be further verified by mutant protein function cell model and animal model.